Trophic ecology of speckled peacock bass Cichla temensis Humboldt 1821 in the middle Negro River, Amazon, Brazil. Issue 4 (1st July 2018) - Aguiar‐Santos, Jamerson; deHart, Pieter A. P.; Pouilly, Marc; Freitas, Carlos E. C.; Siqueira‐Souza, Flávia K.
Abstract: The aim of this study was to analyse the trophic ecology of speckled peacock bass Cichla temensis inhabiting two tributaries of the middle Negro River, the Aracá River and the Demeni River. Using an analysis of stomach contents and stable isotope composition (δ 15 N, δ 13 C) of scales, we describe the diet and evaluate the trophic position of subadult and adult individuals. We then test whether diet shifts and trophic positions occurred among successive size classes and among sample locations. The stomach content analysis confirmed the piscivorous feeding habit of the species and showed that the speckled peacock bass preyed on a variety species belonging to different trophic guilds. The length of the ingested prey increased with the size of the speckled peacock bass. Diet composition and trophic position were not different among size classes. δ 13 C values yielded significant shifts among the size classes: larger individuals displayed higher δ 13 C values than smaller individuals. Trophic position varied between locations, with lowest values observed in fish from the Aracá River. This study demonstrated that diet of C. temensis may vary according to the size of the fish, even at the subadult or adult stages, and according to the river/locality, even within a same basin. We then suggest that further studies take into account local availability of food resources to better explore C. temensis diet and tropic ecology.